2000
DOI: 10.1007/s002130000529
|View full text |Cite
|
Sign up to set email alerts
|

Zolmitriptan (a 5-HT1B/1D receptor agonist with central action) does not increase symptoms in obsessive compulsive disorder

Abstract: Based upon these findings, no evidence was found for a specific role of the 5-HT1B/1D receptor in OCD. It should be noted, however, that challenge studies in OCD are difficult to perform. Perhaps in the future better challenge paradigms will make it possible to further explore the role of specific receptor types in OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…This is a potential confounder of the data in that the drug may itself produce changes in brain structure and function, albeit intermittent use with the use with migraine attacks. While the direct effects of triptans are still a matter of debate (Tfelt-Hansen 2010), and longitudinal studies will be needed to clarify their impact on the central nervous system central nervous system central nervous system, there are studies supporting direct effects of triptans on CNS (Boshuisen and den Boer 2000; Cupini and Calabresi 2005; Dodick and Martin 2004). …”
Section: Discussionmentioning
confidence: 99%
“…This is a potential confounder of the data in that the drug may itself produce changes in brain structure and function, albeit intermittent use with the use with migraine attacks. While the direct effects of triptans are still a matter of debate (Tfelt-Hansen 2010), and longitudinal studies will be needed to clarify their impact on the central nervous system central nervous system central nervous system, there are studies supporting direct effects of triptans on CNS (Boshuisen and den Boer 2000; Cupini and Calabresi 2005; Dodick and Martin 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CP94253 dose-dependently reduces the expression of conditioned freezing (McDevitt et al, 2011), suggesting that 5-HT 1B R agonists attenuate conditioned anxiety. Clinical research investigating the effects of the triptan class of 5-HT 1 R agonists on anxiety has yielded mixed result with some studies reporting no effects of acute administration of sumatriptan, a 5-HT 1A/1B/1D R agonist (Pian et al, 1998), or zolmitriptan, a 5-HT 1B/1D/1F R agonist (Boshuisen and den Boer, 2000) in patients with obsessive-compulsive disorder (OCD). However, others have reported symptom exacerbation in OCD patients using the same acute doses (Stern et al, 1998) and following chronic administration (Koran et al, 2001), suggesting that 5-HT 1B R agonists may be counter indicated for patients with OCD.…”
Section: Dysregulation Of 5-ht1brsmentioning
confidence: 99%
“…Prepulse inhibition (PPI) is an operational measure of sensorimotor gating and refers to the reduction in startle magnitude that occurs when an abrupt startling stimulus is preceded 30–500 msec by a barely detectable stimulus (8), and is reduced in OCD (6, 7). Second, pharmacological challenge with serotonin 1B receptor (5-HT 1B R) agonists exacerbates symptoms in OCD patients (911) (however, see (12)). Third, OCD patients exhibit overactivity of the orbitofrontal cortex (OFC) at rest (1315) and following symptom provocation (16, 17) that is reversed by successful treatment (1820).…”
Section: Introductionmentioning
confidence: 99%